An assessment of k-workers among SMIs in Malaysia - Md Dahalin, Zulkhairi; Ali, Juhary; M.J., Mohd Zukime (2004)
This paper is based on a research study to assess the development of human resource based on the application of Information Technology in the industrial sector, specifically the small-medium enterprises in Malaysia.This is a field study in the form of a survey research using a cross-sectional approach where a sample of SMIs representing the production and manufacturing firms listed in the Federation of Malaysian Manufacturers were sought.Sampling technique in the form of proportionate random sampling was used taking into account the different sample frame sizes according to the industries.A total of 200 firms were selected in which questionnaires were sent and 84 usable returns were received representing a 42 percent response.Results of the study showed a small number of K-Workers present in the SMI firms with only 33 percent of the firms in the sample reported having knowledge workers. There is also a low degree of technology and IT adoption among the SMI firms with only half of the firms invested in technology and/or IT.However, there is a positive indication towards increasing the number of K-Workers among SMIs in the study as all respondents have access to e-mails.This can be seen as a motivating factor towards encouraging more SMIs to adopt IT and changing the way employees perform their business activities moving towards achieving the long-term competitiveness in the knowledge economy.